Automatic Number Plate Recognition (ANPR) of Vehicle using Image processing and Graph based Pattern Matching - Ghosh, Bibek Ranjan; Banerjee, Siddhartha; Pramanik, Prithviraj; Dey, Soham (International Journal of Computer Sciences and Engineering, 2015)
Automatic Number Plate Recognition (ANPR) is a real time embedded system which identifies the characters directly from the image of the license plate. Since different standard are used in different country, automatic number plate recognition system is different for each country. In this paper, a number plate recognition system for vehicles in India is proposed. This paper introduces a vehicle number plate identification system, which extracts the characters features of a plate, from an image captured by a digital camera. The system uses broad steps like thresholding, image segmentation, thinning and pattern matching for extraction of characters. The pattern matching is done using graph based method. Graph matching techniques are introduced to compute the similarity of characters extracted from number plate with the information of characters store in the database.